Crisis? Let's digitize! How the crisis situation affected the processes of digitalization in the Croatian History Museum (Libellarium: journal for research in the field of information and related sciences, 2022)
Purpose. The aim of this paper is to analyse the possibilities of using existing digitization projects, as well as designing new ones, in the context of challenges caused by the pandemic and the earthquakes. The paper deals with the Croatian History Museum (CHM) response to a complex crisis situation caused by the SARS – CoV-2 virus pandemic and a strong earthquake that hit Zagreb on March 22, 2020. As a result of these events, the Croatian History Museum is at present closed to the public until further notice and faces a challenge of finding new models of communication with users in order to fulfil its purpose and mission.Approach/methodology. The methodology of the work will focus on the analysis of previous projects and the use of digitization processes and digital copies as the exclusive and only central approach in processing, ensuring accessibility and in the presentation of museum material in crisis situations, with emphasis on new ways of its use and the improvement of the existing communication of the Museum with its users.Findings. The paper provides a detailed account of the importance of digitalization processes and digital copying and their implementation in the design of new business process models with the possibility of establishing new services and communication with users in a virtual environment.Originality. The originality of this paper is reflected in the fact that the experience gained from these projects can serve the Croatian History Museum and other heritage institutions in the Republic of Croatia in the practical application of one of the models of using digitalization in overcoming numerous challenges, especially in crisis situations that heritage institutions are facing today.
Keywords: digitalization; heritage protection; museum documentation; museum library; preservation